Structural modification of Clusianone from Garcinia parvifolia and in vitro evaluation targeting microtubule system of respiratory carcinoma - Nagalingam, Sree Vaneesa (2017)
Clusianone isolated from Garcinia parvifolia has been studied for its anticancer properties and cytotoxicity to human respiratory cells. The clusianone was first isolated using solvent extraction, column chromatography, thin layer chromatography and finally recrystallization method through solvent evaporation including seed crystal to induce crystal growth of clusianone. The clusianone was characterized using X-ray crystallography, ESI-MS, NMR and melting point. During the course of this research, clusianone was chemically modified and eight different derivatives abbreviated as CMet, CHyd, CMxA, CMeA, CEtA, CPryl, CGeryl and CDMet were obtained. Some of the chemical methods employed were hydrogenation, methylation, demethylation, ketone reduction via addition of amine derivatives and O-alkylation to install additional prenyl and geranyl chain into clusianone. Further studies of the role of the clusianone derivatives were presented in its in vitro anticancer activity. The anticancer test and cytotoxicity effect were tested using MTT(3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide)assay. Specific normal human and cancer cell lines were used in the assay being MRC5 (lung fibroblast), A549 (lung adenocarcinoma, NP69 (nasopharyngeal epithelial cell and HK1 (squamous carcinoma of the nasopharynx). Preliminary study of clusianone and derivatives showed cytotoxicity effect in dose dependent manner. Based on the results, clusianone and compound CMeA demonstrated good anticancer activity showing IC50 values below 5 μM against A549 and HK1 cancer cells and at the same time affecting less of the MRC5 and NP69 normal cells. Western blot method was employed to further elucidate the downregulation of the protein expression of β-tubulin including cell cycle regulators Cdk1 and cyclin B1 for clusianone and CMeA derivative treated carcinoma cells. Clusianone and compound CMeA demonstrated potential antimicrotubule agent characteristic since expression of β-tubulin and cell cycle regulators Cdk1/cyclin B1 were downregulated in A549 cells. As for HK1 cells, clusianone downregulated β-tubulin protein without affecting Cdk1 and cyclin B1 expression. In contrast, compound CMeA showed prominent downregulation of β-tubulin, CDK1 and cyclin B1 proteins especially after 48 hours treatment in HK1 cells.